2010
DOI: 10.1002/pros.21240
|View full text |Cite
|
Sign up to set email alerts
|

Targeting prostate cancer angiogenesis through metastasis‐associated protein 1 (MTA1)

Abstract: MTA1 pro-angiogenic and pro-invasive functions create permissive environment for PCa tumor growth and likely support metastasis. Taken together with its predictive values, MTA1 can be utilized both as a prognostic marker and a therapy target in PCa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
117
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 81 publications
(127 citation statements)
references
References 54 publications
8
117
0
1
Order By: Relevance
“…Western blot analysis was carried out as described previously (Butt et al ., 2017; Dhar et al ., 2015a,b, 2016, 2017; Dias et al ., 2013a,b; Kai et al ., 2010, 2011; Li et al ., 2013). The antibodies used in this study are listed in Table S1.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Western blot analysis was carried out as described previously (Butt et al ., 2017; Dhar et al ., 2015a,b, 2016, 2017; Dias et al ., 2013a,b; Kai et al ., 2010, 2011; Li et al ., 2013). The antibodies used in this study are listed in Table S1.…”
Section: Methodsmentioning
confidence: 99%
“…In our previous studies, we have identified metastasis‐associated protein 1 (MTA1) as a novel factor involved in ‘vicious cycle’ of prostate cancer cells interacting with bone cells, and hypothesized that MTA1 may play a specific role in prostate cancer bone metastasis (Kai et al ., 2011). Our following studies validated high MTA1 expression in advanced metastatic prostate cancer and bone lesions of patients with prostate cancer (Dias et al ., 2013a; Kai et al ., 2011).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations